Development of a high-value care culture survey: a modified Delphi process and psychometric evaluation. Issue 6 (26th October 2016) - Gupta, Reshma; Moriates, Christopher; Harrison, James D; Valencia, Victoria; Ong, Michael; Clarke, Robin; Steers, Neil; Hays, Ron D; Braddock, Clarence H; Wachter, Robert
Abstract : Background: Organisational culture affects physician behaviours. Patient safety culture surveys have previously been used to drive care improvements, but no comparable survey of high-value care culture currently exists. We aimed to develop a High-Value Care Culture Survey (HVCCS) for use by healthcare leaders and training programmes to target future improvements in value-based care. Methods: We conducted a two-phase national modified Delphi process among 28 physicians and nurse experts with diverse backgrounds. We then administered a cross-sectional survey at two large academic medical centres in 2015 among 162 internal medicine residents and 91 hospitalists for psychometric evaluation. Results: Twenty-six (93%) experts completed the first phase and 22 (85%) experts completed the second phase of the modified Delphi process. Thirty-eight items achieved ≥70% consensus and were included in the survey. One hundred and forty-one residents (83%) and 73 (73%) hospitalists completed the survey. From exploratory factor analyses, four factors emerged with strong reliability: (1) leadership and health system messaging (α=0.94); (2) data transparency and access (α=0.80); (3) comfort with cost conversations (α=0.70); and (4) blame-free environment (α=0.70). In confirmatory factor analysis, this four-factor model fit the data well (Bentler-Bonett Normed Fit Index 0.976 and root mean square residual 0.056). The leadership and health system messaging (r=0.56, p<0.001), data transparency and access (r=0.15, p<0.001) and blame-free environment (r=0.37, p<0.001) domains differed significantly between institutions and positively correlated with Value-Based Purchasing Scores. Conclusions: Our results provide support for the reliability and validity of the HVCCS to assess high-value care culture among front-line clinicians. HVCCS may be used by healthcare groups to identify target areas for improvements and to monitor the effects of high-value care initiatives.